Science Policy Training for a New Physician Leader: Description and Framework of a Novel Climate and Health Science Policy Fellowship. Issue 3 (1st April 2019) - Lemery, Jay; Sorensen, Cecilia; Balbus, John; Newman, Lee; Davis, Christopher; Reno, Elaine; Salas, Renee; Hynes, Emilie Calvello
Abstract: The accelerating health impacts of climate change are undermining global health, and the roles of the health sector in addressing the many challenges of climate change are being articulated by governments, multilateral institutions, and professional societies. Given the paucity of physician engagement on this issue to date, there now exists a clear need for health professionals to meet this new challenge with the development and cultivation of new knowledge and skill sets in public health, environmental science, policy, and communication. We describe a novel GME fellowship in climate and health science policy, designed to train a new generation of clinicians to provide the necessary perspective and skills for effective leadership in this field. This fellowship identifies available university resources and leverages external collaborations (government, medical consortiums, affiliate institutions in public health, and environmental science), which we describe as being replicatable to similar training programs of any number of medical specialties and likewise bring meaningful opportunities to their respective training programs and academic departments. The creation of this novel fellowship in climate and health policy provides a roadmap and potential path for similar programs to join us in addressing the defining health issue of this generation and many to follow.